A comparative study between theory & practices: role of Windmill Advertising Ltd. on holistic approach for market penetration of mobile financial services of Mercantile Bank Ltd. - Sabah, Rahnuma Akram (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2014.